Current trend of state responsibility in processes of unjust deprivation of liberty proffered by the Third Section of the Council of State in the years 2016-2017 - Ramírez Rivas, Andrea Del Pilar (DIXI, 2019)
Purpose: In Colombia, there is a recurring problem of mass detentions, and arbitrary practices and inappropriate use of power have become increasingly frequent when a citizen is deprived of his or her liberty. The social state under the rule of law is founded on the dignity of the human person and cannot therefore be structured or operate based on ignorance of the rights of individuals.Methodology: Defining the lines of jurisprudence and the scope of patrimonial responsibility in actions for direct reparation in processes of unjust deprivation of liberty in the Third Section of the Council of State acquires importance from the point of view of the legal sciences. This is because it is necessary to have conceptual clarity on the current recognition of extra-patrimonial damages in Colombia.Findings: This is causing problems for the state, including claims for state responsibility, generating a patrimonial detriment.Conclusions: Subjecting legal procedures to the fundamental principles of law is the safest way to avoid failures or violations of rights that subsequently generate the state’s obligation to assume responsibility and repair damages by means of compensation for damages, whether these are patrimonial or extra-patrimonial.
Keywords: Social state under the rule of law; unjust deprivation of liberty; direct reparation; state responsibility